OPTIMIZING RESOURCE ALLOCATION IN EBONYI STATE SCHOOLS USING BIG DATA ANALYTICS (IJOVTECH, 2026)
This paper examines how big data analytics can be used to maximize resource utilization in schools in Ebonyi State, Nigeria, in solving the endemic problems of unequal and inefficient provision of education. Based on the primary data collection strategy in the form of surveys and interviews with school administrators, teachers, and students, the study focuses on the distribution of financial, human, and material resources on limited budgets and the increasing number of students under the value of comprehensive data-driven models. The background sheds light to the educational inequalities in Nigeria, especially in the Ebonyi State where the public secondary schools are underfunded and ill-equipped in terms of the infrastructure they utilize as developed by the budgetary allocation who is lesser than the UNESCO standards. The problem statement highlights the existence of inefficiencies in the use of resources that results to poor learning outcomes, high rates of dropout, and inequitable access. Extensive literature review combines outdated views of the 1980s and 1990s regarding the issues with resource constraints in the education of Nigeria and the recent research of predictive analytics and personalized learning by applying the concept of big data. The present study based on the Resource-Based Theory and Data-Driven Decision-Making framework was built as a mixed-methods research design, where 1,200 participants provided their demographic data and the results revealed a teacher-student ratio of 1:60 in most schools and the level of literacy as depending on the socioeconomic factors of the population. Results indicate that big data tools reduced the unequal distribution of resources by up to 40 percent to enhance performance metrics in students. Concluding, the paper proposes changes to the policy that can be undertaken to incorporate analytics in state education planning with the focus on scaleable digital infrastructure. The article can make contributions to the general research by filling the gap between technology and education policy in developing settings.